Effectiveness of crizotinib in a patient with mesenchymal-epithelial transition overexpression/fluorescence in situ hybridization-negative/next-generation sequencing-negative advanced lung adenocarcinoma: a case report - Song, Peng; Liu, Li; Liu, Yutao; Zhang, Tao; Guo, Lei; Li, Weihua; Ying, Jianming; Yang, Lin; Gao, Shugeng (Translational Cancer Research, 2019)
Crizotinib, an oral ATP-competitive tyrosine kinase inhibitor (TKI), has shown significant activity against advanced non-small cell lung cancer (NSCLC) tumors harboring mesenchymal-epithelial transition (MET) amplification or exon 14 mutation. Methods to detect MET alteration includes immunohistochemistry (IHC), fluorescence in situ hybridization (FISH), next-generation sequencing (NGS) and reverse transcription polymerase chain reaction (RT-PCR). Despite multiple methods for detecting MET alteration, the response to crizotinib in advanced NSCLC patients according to the results of MET IHC staining is still unknown. This case showed effectiveness of crizotinib in a pretreated patient with advanced lung adenocarcinoma detected as MET overexpression/FISH-negative/NGS-negative. MET overexpression might be a biomarker for predicting efficacy of crizotinib.